2022 EULAR points to consider for remote care in rheumatic and musculoskeletal diseases. Issue 8 (25th April 2022) - de Thurah, Annette; Bosch, Philipp; Marques, Andrea; Meissner, Yvette; Mukhtyar, Chetan B; Knitza, Johannes; Najm, Aurélie; Østerås, Nina; Pelle, Tim; Knudsen, Line Raunsbæk; Šmucrová, Hana; Berenbaum, Francis; et al.
Abstract : Background: Remote care and telehealth have the potential to expand healthcare access, and the COVID-19 pandemic has called for alternative solutions to conventional face-to-face follow-up and monitoring. However, guidance is needed on the integration of telehealth into clinical care of people with rheumatic and musculoskeletal diseases (RMD). Objective: To develop EULAR points to consider (PtC) for the development, prioritisation and implementation of telehealth for people with RMD. Methods: A multidisciplinary EULAR task force (TF) of 30 members from 14 European countries was established, and the EULAR standardised operating procedures for development of PtC were followed. A systematic literature review was conducted to support the TF in formulating the PtC. The level of agreement among the TF was established by anonymous online voting. Results: Four overarching principles and nine PtC were formulated. The use of telehealth should be tailored to patient's needs and preferences. The healthcare team should have adequate equipment and training and have telecommunication skills. Telehealth can be used in screening for RMD as preassessment in the referral process, for disease monitoring and regulation of medication dosages and in some non-pharmacological interventions. People with RMD should be offered training in using telehealth, and barriers should be resolved whenever possible. The level of agreement to each statement ranged from 8.5 to 9.8/10. Conclusion: The PtC have identified areas where telehealth could improve quality of care and increase healthcare access. Knowing about drivers and barriers of telehealth is a prerequisite to successfully establish remote care approaches in rheumatologic clinical practice.